Analisis Organisasi Remas (Remaja Masjid Riyadhul Jannah) Desa KD Kampil: Tantangan Dan Pengaruh Terhadap Keterlibatan Anggota - Farah Fadiyah; Wahyu Eko Pujianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze the Remas Organization (Riyadhul Jannah Mosque Youth) KD Kampil Village, which was founded at the end of 2020. The problems that are the focus of the research include the lack of involvement of members, especially female members, lack of initiative from youth, and internal problems in monthly deliberations. The research methods used were participatory observation, interviews with the Head of the Organization, Ahmad Syafi'udin, and analysis of documentation related to organizational activities. The research results show that the lack of involvement of female members is influenced by the large number of female members who are married, while the lack of youth initiative is caused by the workload of young people who are already working. Internal problems in monthly deliberations involve disagreements between members and inconsistent attendance. Proposed improvement efforts include increasing the involvement of female members through special programs, encouraging youth initiative through leadership training activities, and improvements in the deliberation process to increase the effectiveness of meetings and minimize conflict. It is hoped that this research can contribute to improving the performance and involvement of members in the KD Kampil Village Remas Organization.